Implementation Outcomes of Literacy Movement trough The Habituation, Development and Learning Stages for Indonesian Elementary School Students - Nurhasanah, Nurhasanah; Rahman, Rahman; Nugraha, Trisna (International Conference on Elementary Education, 2021)
The Indonesian government has implemented awareness of literacy's importance through the school literacy movement at every level of education. The literacy movement, especially at the elementary school level, is carried out in three stages. There are habituation, development, and learning. The literacy movement's implementation since 2016 at the elementary school level has carried out well. However, there are still some obstacles. The method used is a systematic literature review. It examines various reports of literacy stakeholders in their implementation against each context. These reports found different effective strategies for successfully implementing the literacy movement, which can use as references. It then discovered that various obstacles became the gap in literacy education in Indonesia to be minimized further. This systematic literature review highlights a need to implement meaningful and innovative strategies by utilizing stakeholders such as teachers, school principals, parents, communities, and teacher institutes to provide professional context-based input related to the literacy movement